New Approaches to Identifying and Reducing the Global Burden of Disease From Pollution. (25th March 2020) - Filippelli, Gabriel; Anenberg, Susan; Taylor, Mark; van Geen, Alexander; Khreis, Haneen
Abstract: Pollution from multiple sources causes significant disease and death worldwide. Some sources are legacy, such as heavy metals accumulated in soils, and some are current, such as particulate matter. Because the global burden of disease from pollution is so high, it is important to identify legacy and current sources and to develop and implement effective techniques to reduce human exposure. But many limitations exist in our understanding of the distribution and transport processes of pollutants themselves, as well as the complicated overprint of human behavior and susceptibility. New approaches are being developed to identify and eliminate pollution in multiple environments. Community‐scale detection of geogenic arsenic and fluoride in Bangladesh is helping to map the distribution of these harmful elements in drinking water. Biosensors such as bees and their honey are being used to measure heavy metal contamination in cities such as Vancouver and Sydney. Drone‐based remote sensors are being used to map metal hot spots in soils from former mining regions in Zambia and Mozambique. The explosion of low‐cost air monitors has allowed researchers to build dense air quality sensing networks to capture ephemeral and local releases of harmful materials, building on other developments in personal exposure sensing. And citizen science is helping communities without adequate resources measure their own environments and in this way gain agency in controlling local pollution exposure sources and/or alerting authorities to environmental hazards. The future of GeoHealth will depend on building on these developments and others to protect a growing population from multiple pollution exposure risks. Plain Language Summary: The health burdens of legacy contaminants, and the continuing global health burdens of current pollution, are crippling both global health and well‐being. Much of the exposure science on these relatively well‐studied pollutants is known, as is the general toxicity of past pollutants. But there is a great distance between understanding the toxicity and exposure sources of environmental pollutants and applying that knowledge in practical and just ways. This contribution summarizes several major repositories and ongoing sources of soil, dust, and air pollution and addresses the harmful effects from exposure to these. We also highlight some examples of the future of GeoHealth research in this area by providing case studies of current novel approaches that focus on bridging the science of pollution sources and distribution with real applications at the community level to reduce pollution's role in the global burden of disease. Key Points: Legacy and current pollutants are a major global cause of disease and death Many detection and mitigation tools are not adequate for identifying pollution hot spots in communities, particularly vulnerable ones The next century of AGU will usher in novel, community‐focused techniques and approaches to mapping pollutants and reducing exposure